International multi-site initiative to develop an MRI-inclusive nomogram for side-specific prediction of extraprostatic extension of prostate cancer - Wibmer, Andreas G.; Kattan, Michael W.; Alessandrino, Francesco; Baur, Alexander Daniel Jacques; Boesen, Lars; Franco, Felipe Boschini; Bonekamp, David; Campa, Riccardo; Cash, Hannes; Catalá, Violeta; Crouzet, Sebastien; Dinnoo, Sounil; et al. (Cancers, 2021)
For patients with newly diagnosed prostate cancer, it is important to detect tumor growth beyond the prostate, as this can affect a patient’s prognosis, influence management decisions, and alter treatment strategies. It is recognized that on prostate MRI, some instances of extraprostatic tumor growth can be missed. In this study, we merged patient data from multiple hospitals in different countries and developed a type of mathematical formula called “nomogram” that combines MRI findings with other available patient data. The results of our study allow physicians to more accurately diagnose extraprostatic tumor growth by combining clinical, biopsy, and MRI-derived information according to their relative statistical importance.
Gesehen am 20.07.2022